Occupational Role Stress: a Study of Indian Business Process Outsourcing Employees - Aziz, Mohsin (Mediterranean Journal of Social Sciences, 2012)
The fierce competition among multinationals to reduce cost has forced many organisations to shift their non core operations tolow cost and high quality destinations like India. This has resulted in exponential growth in the number of business process outsourcingcentres in India. It mainly deals with customer interaction services, human resources, data search/integration etc. under the aegis ofBusiness Process Outsourcing (BPO).The employees work in prolonged shifts round the clock. To provide real-time services to globalcustomers they have to compromise with their own biological clock. Consequently they become easy prey to various psychophysiologicalailments. Researches have revealed that psychological stress and its physiological symptoms are the most commonproblems amongst call-centre executives (Luce & Juravich, 2002).Occupational Role Stress Scale (Pareek, 1983) will be used to find thelevel of role stress among the call centre employees. Student’s t-test will be used for analysis purpose. The study is expected to identifystress related issues being faced by call centre employees.